Evaluation of Functionally Graded Architecture using Fused Filament Fabrication Technique for Bone Scaffold Applications - Noordin, Muhammad Azfar; Zulkipli, Mohd Aidil Syukri; Kadir Hussein, Nur Aqila; Md Saad, Amir Putra (International Journal of Integrated Engineering, 2022)
Bone scaffold architecture affects the performance of bone scaffold significantly. Recently, functionally graded architecture (FGA) has received wide attention in bone scaffold application due to its architecture that mimics the cancellous bone architecture. Hence, this study aims to evaluate the mechanical properties of PLA specimens that adopt FGA fabricated using additive manufacturing via fused fabrication filament (FFF). The mechanical properties of FGA PLA specimen (1 GPa -2 Gpa) was tailored to the cancellous bone (modulus: 0.01 GPa – 2 GPa). The result shows that Radially dense- in rod (RDR) has the highest Young’s Modulus, and yield strength. However, the relationship between cross section area of specimen need to be considered in comparing the performance of FGA PLA specimen.